2002
DOI: 10.1001/jama.287.23.3143
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Mood and Empathy During Internship

Abstract: We found that, in this sample, enthusiasm at the beginning of internship soon gave way to depression, anger, and fatigue. Future research should be aimed at determining whether these changes persist beyond internship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

26
262
4
17

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 341 publications
(309 citation statements)
references
References 17 publications
26
262
4
17
Order By: Relevance
“…Despite rigorous research, there is still increasing concern among medical educators and medical professionals regarding the decline in medical students' empathy during medical education. (Bellini et al, 2002, Chen et al, 2007, Hojat et al, 2004, Newton et al, 2008, Sherman and Cramer, 2005 Some studies suggest that the decline is mostly pronounced in the later years while others suggest that it occurs in the early years of medical education. (Austin et al, 2007;Hojat et al, 2009) Varying designs, employing varying instruments, have been used.…”
Section: The Power Of Empathymentioning
confidence: 99%
“…Despite rigorous research, there is still increasing concern among medical educators and medical professionals regarding the decline in medical students' empathy during medical education. (Bellini et al, 2002, Chen et al, 2007, Hojat et al, 2004, Newton et al, 2008, Sherman and Cramer, 2005 Some studies suggest that the decline is mostly pronounced in the later years while others suggest that it occurs in the early years of medical education. (Austin et al, 2007;Hojat et al, 2009) Varying designs, employing varying instruments, have been used.…”
Section: The Power Of Empathymentioning
confidence: 99%
“…2,7 Anxiety, depression, and problematic alcohol use are among the mental health issues experienced by medical residents. A recent systematic review and meta-analysis 6 including 54 studies from five continents identified an overall pooled prevalence of depression or depressive symptoms of 28.8% among medical residents, ranging from 20.9 to 43.2%, depending on the instrument used.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found high levels of stress and burnout among residents (from depression and problematic patient care) and that aspects of residency training that correlate with resident satisfaction include clear management, adequate feedback, a right to a voice in important matters, and a culture of openness and tolerance; while burnout and emotional exhaustion co-sort with inherently difficult job situations, stress in relationships with faculty and senior residents, and perceptions of work as stressful. [37][38][39][40] It is likely that the positive effect on resident morale contributes to lower resident stress and burnout in programs where chief residents completed CRTP.…”
Section: Discussionmentioning
confidence: 99%